IXODOFAUNA E SEUS AGENTES INFECCIOSOS NO PARQUE DA LAGOA COMPRIDA DO MUNICÍPIO DE AQUIDAUANA/MS, BRASIL - Joelly Corrêa dos Santos (2024)
Ticks are obligatory blood-feeding ectoparasites that infest a variety of vertebrate animals and have the potential to transmit viruses, bacteria, and protozoa. This study aimed to investigate the tick fauna and their infectious agents in the Parque Natural da Lagoa Comprida (PNMLC), in the municipality of Aquidauana, Mato Grosso do Sul, Brazil. The ticks were collected through flag dragging and active search/visual inspection. After collection, the ticks were stored in 70% ethanol and sent to the Tick Biology Laboratory at Embrapa Gado de Corte, for taxonomic identification. The samples were then subjected to DNA extraction, PCR, and sequencing, to detect the presence of the infectious agents Rickettsia spp., Borrelia spp., and Babesia spp. The 1.216 ticks found were identified as Amblyomma sculptum and Amblyomma dubitatum. Among these, 31 samples, representing 2.55% of the total, tested positive for the protozoan Babesia. Notably, one of these positive samples showed 100% similarity to the species Babesia bigemina, originating from a tick of the species A. sculptum. This research work provides valuable information within the scope of One Health, thus contributing to the discovery of different infectious agents in tick species not previously reported to be associated with such pathogens.